Determination of muzakki's interest on zakat in amil zakat institution - Isnaeni Nurul Janah; Dina Yustisi Yurista; Mohammad Noviani Ardi (Department of Islamic Economic, Faculty of Economic and Business, Nahdlatul Ulama Islamic University (UNISNU) Jepara, Indonesia, 2023)
This study aims to determine the factors behind the interest of donors in paying Zakat, Infaq and Shadaqah at LAZ Nurul Hayat and then test and analyze these factors to find the results of determination. The method in this study is a quantitative method, the subject of the study is a person who pays zakat (muzakki) at the Amil Zakat Nurul Hayat Institute. The data collection method using a questionnaire that was distributed to 100 respondents while the data analysis method used in this study was descriptive analysis and regression analysis. The results showed that the factors that influence the interest of donors in paying zakat, Infaq and Shadaqah in Nurul Hayat Semarang are promotion, distribution and transparency. Meanwhile, of the three variables that are most influential or the most dominant in the interest of donors in paying zakat infaq and shadaqah at the Amil Zakat Nurul Hayat Institution in Semarang are promotional variables. The results of this study are expected to be used as guidelines for the Amil Zakat Agency and the Amil Zakat Institution in making programs to increase the number of muzaki and the receipt of zakat funds